Towards better estimates of uncorrected presbyopia - Holden, Brien A; Tahhan, Nina; Jong, Monica; Wilson, David A; Fricke, Timothy R; Bourne, Rupert; Resnikoff, Serge (Bulletin of the World Health Organization, 2015)
[web URL: http://www.who.int/entity/bulletin/volumes/93/10/15-156844/en/index.html]